Las políticas de desarrollo regional en Ecuador - Correa Quezada, Ronny (2016)
The regional economic development perspective has been present in various forms and scopes in Latin America. This article proposes the analysis of Ecuador, a country with very particular historical, economic and political conditions that constructed very specific ways for the process of designing and implementing regional policy. The goal is to identify and scope that public policy had in the context of adopted economic development models considering the strategies and approaches that the government used to address regional problems and territorial economic development.